4x-6+2=2(3x-4)

Simple and best practice solution for 4x-6+2=2(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6+2=2(3x-4) equation:



4x-6+2=2(3x-4)
We move all terms to the left:
4x-6+2-(2(3x-4))=0
We add all the numbers together, and all the variables
4x-(2(3x-4))-4=0
We calculate terms in parentheses: -(2(3x-4)), so:
2(3x-4)
We multiply parentheses
6x-8
Back to the equation:
-(6x-8)
We get rid of parentheses
4x-6x+8-4=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2

See similar equations:

| 115-u=213 | | 9x-3=19=2x | | 10+4x=x+46 | | 7x-25=20+2x | | 26=245-x | | x3+3x2–10x=0 | | 2.1q-5.6-2.3q=1.2q-4.5 | | 6a^2+11-7=0 | | 6y=3(-2y)+12 | | a|1.23=0.2 | | 126=-6(-2+n) | | |5x|+2=52 | | (9x+6/12)+(8x-4/12)=3 | | −3=k−7 | | (x+x+5)30=3450 | | 1/7x+15=42 | | 173=-6n-7(-7n+6) | | ​3x-8=3(x-4)+1 | | 9x+6/12+8x-4/12=3 | | -3(3s-6)-18=-3(5s+3)-3 | | 2x=519 | | 4+3r-5=6+2r+4 | | x²-6x-187=0 | | 8-4n=-8 | | −24−18p=38pp= | | 10+6x=15+9x–3 | | (3x+10)^0=(6x-14)^0 | | A-2a-6=-5 | | -6x+56=28+3(7+1/3x) | | (9x+6)+(8x-4)=3 | | -2x+2=4-6(x-5) | | 6x–(3x+8)=4x–x+8 |

Equations solver categories